SUPPLY CHAIN MANAGEMENT ANALYSIS OF MINICONT-Mini Folding Container AS THE WORLD NEXT LOGISTIC SOLUTION IN PT. PELINDO MARINE SERVICE SURABAYA - GHAZALIE GHAZALIE; ARIS SARJITO; YUSUF ALI; SISWO PUDJIATMOKO (Journal of International Conference Proceedings (JICP), 2019)
Logistics and Supply Chain Management have a very important role in the regulation of maritime transportation both in Indonesia and the world because it becomes a barometer for determining the prices of goods and services to consumers. The current phenomenon in Indonesia is that logistics costs are the highest in the world when compared to Malaysia, which is only 15%, and the US and Japan are 10% respectively. In addition to very high costs, the quality of logistics services in our country is also not optimal. This condition is made an opportunity by PT. Pelindo III through its subsidiary PT. Pelindo Marine Service (PMS) which is engaged in logistics services based in Surabaya innovates to make MiniCont-Mini Folding Container. Based on our research that this MiniCont can reduce logistics costs by up to 30% and can be used as a global future logistics solution. This study uses a qualitative approach to analyze the extent to which efficiency of reduced logistics costs.This product is the result of the synergy between PT. Pelindo Marine Service (PMS) and PT. Semen Indonesia Logistik (SILOG).